EFEKTIVITAS PROBLEM BASED LEARNING BERBANTU SOFTWARE GEOGEBRA PADA MATERI PROGRAM LINEAR TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SMA - Lia Lalita Giovanti; Achmad Buchori; Noviana Dini Rahmawati (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
The purpose of this research is to 1). Knowing that there are differences in students' mathematical communication abilities with the Problem Based Learning (PBL) learning model assisted by GeoGebra Software and conventional learning models. 2) Find out which learning model is better between the Problem Based Learning (PBL) learning model assisted by GeoGebra Software and the conventional learning model for students' mathematical communication abilities. 3) To determine the influence of student activity on students' mathematical communication skills who use the PBL (Problem Based Learning) learning model assisted by GeoGebra Software. 4) To find out whether students' mathematical communication skills who use the Problem Based Learning (PBL) learning model assisted by GeoGebra Software achieve individual or classical mastery. The research method used in this research is the Quasi Experimental method. The sampling technique uses purposive sampling technique. The instruments for collecting data in this research are Pre-test and Post-test. . The population of this study were class XI students of SMAN 1 Wedung. The N-Gain test is the data analysis technique used in this research. The results of this research show that the N-Gain score in the experimental class (PBL method assisted by GeoGebra) is 62%. Meanwhile, the N-Gain score in the control class (conventional method) was 54%. In other words, it can be concluded that the mathematical communication skills of students who received PBL learning assisted by GeoGebra were significantly more effective than students who received learning using the conventional method